MONOGRAFI DESA NUNGGALREJO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH TAHUN 2014 - Sunardi Sunardi; Sudarmi Sudarmi; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2016)
This study aimed to determine the condition of the economy, population, education, and social cultural village. The research method used was descriptive research method. The object of this study was the condition of the economy, population, education, social cultural. Data were collected by documentation and interview techniques. The analysis in this study used descriptive qualitative data analysis. The conclusion from this research were: (1) The Economic circumstances was that majority of the population are mostly work as cane/bamboo craftsmen as many as 450 people (13.46%) (2) The population is as many as 4226 people (3) Education is as many as in 2138 (50.59%) of elementary school education (4) Social Cultural Nunggalrejo village residents are included in heterogeneous cultural pattern, but still under the influence of Sundanese ethnic cultural domination.Penelitian ini bertujuan untuk mengetahui keadaan ekonomi, kependudukan, pendidikan, dan sosial budaya. Metode penelitian yang digunakan adalah metode penelitian deskriptif. Objek penelitian ini yaitu keadaan ekonomi, kependudukan, pendidikan, sosial budaya di Desa Nunggalrejo Kecamatan Punggur Kabupaten Lampung Tengah. Pengumpulan data menggunakan teknik dokumentasi dan wawancara. Analisis dalam penelitian ini menggunakan analisis data deskriptif kualitatif. Dari hasil penelitian ini diketahui (1) Keadaaan ekonomi bekerja sebagai pengrajin rotan/ bambu sebanyak 450 jiwa (13,46%) (2) Jumlah penduduk sebanyak 4226 jiwa (3) keadaan pendidikan warga terdapat 2138 (50,59%) berpendidikan Sekolah Dasar (4) Sosial Budaya penduduk termasuk dalam corak kebudayaan yang heterogen namun masih dalam pengaruh dominasi kebudayaan suku sunda.Kata kunci: keadaan ekonomi, kependudukan, pendidikan, sosial budaya